Future of Educational Technology: Artificial Intelligence Trends in Smart Society 5.0 Utilizing Bibliometric Analysis - Ghasa Faraasyatul 'Alam; Maurish Sofie Rahmi Batita; Ramadhana Setiyawan (Fahima, 2026)
The trend of Artificial Intelligence (AI) in education and smart society 5.0 has developed into a lot of literature with various perspectives. In this review paper, insights are sought regarding three important questions: (1) What are the main categories of AI applications explored in the field of education and smart society 5.0? (2) What are the AI trends based on key research topics for the future? and (3) What are the main scopes that are often researched related to AI? Bibliometric analysis of 1000 research papers followed by content analysis of selected articles revealed a comprehensive conceptual structure of existing literature using Publish or Perish (PoP) application and VOSviewer software. AI research for future of educational technology and smart society 5.0 has obtained various interesting findings which can be the main basis for scientific exploration. Research topic explores the world of education and challenges related to AI for future of smart society 5.0. In addition, this review highlights various theories applied with AI literature in the form of research areas that have not been explored further. In summary, this research offers valuable insights for researchers interested in understanding the current state of AI research for education and smart society 5.0 and identifying future research opportunities in this dynamic field.